Behavioral interventions to improve population health outreach for hepatitis C screening: randomized clinical trial. (18th May 2021) - Mehta, Shivan J; Day, Susan C; Norris, Anne H; Sung, Jessica; Reitz, Catherine; Wollack, Colin; Snider, Christopher K; Shaw, Pamela A; Asch, David A
Abstract: Objective: To evaluate whether opt out framing, messaging incorporating behavioral science concepts, or electronic communication increases the uptake of hepatitis C virus (HCV) screening in patients born between 1945 and 1965. Design: Pragmatic randomized controlled trial. Setting: 43 primary care practices from one academic health system (Philadelphia, PA, USA) between April 2019 and May 2020. Participants: Patients born between 1945 and 1965 with no history of screening and at least two primary care visits in the two years before the enrollment period. Interventions: This multilevel trial was divided into two studies. Substudy A included 1656 eligible patients of 17 primary care clinicians who were randomized in a 1:1 ratio to a mailed letter about HCV screening (letter only), or a similar letter with a laboratory order for HCV screening (letter+order). Substudy B included the remaining 19 837 eligible patients followed by 417 clinicians. Active electronic patient portal users were randomized 1:5 to receive a mailed letter about HCV screening (letter), or an electronic patient portal message with similar content (patient portal); inactive patient portal users were mailed a letter. In a factorial design, patients in substudy B were also randomized 1:1 to receive standard content (usual care), or content based on principles of social norming, anticipated regret, reciprocity, and commitment (behavioral content). Main outcome measures: Proportion of patients who completed HCV testing within four months. Results: 21 303 patients were included in the intention-to-treat analysis. Among the 1642 patients in substudy A, 19.2% (95% confidence interval 16.5% to 21.9%) completed screening in the letter only arm and 43.1% (39.7% to 46.4%) in the letter+order arm (P<0.001). Among the 19 661 patients in substudy B, 14.6% (13.9% to 15.3%) completed screening with usual care content and 13.6% (13.0% to 14.3%) with behavioral science content (P=0.06). Among active patient portal users, 17.8% (16.0% to 19.5%) completed screening after receiving a letter and 13.8% (13.1% to 14.5%) after receiving a patient portal message (P<0.001). Conclusions: Opt out framing and effort reduction by including a signed laboratory order with outreach increased screening for HCV. Behavioral science messaging content did not increase uptake, and mailed letters achieved a greater response rate than patient portal messages. Trial registration: ClinicalTrials.gov NCT03712553 .